Simplifying Fabric Flammability Measurements for Use in Public Health Practice (Journal of Fiber Bioengineering and Informatics, 2024)
Fire behavior of textiles varies depending on fiber composition, manufacturing process and any additionaltreatments applied. Such variables can contribute to significant differences in the flammability making itdifficult to estimate the risk of fire ignition. Clothing fires can cause burns with minor injuries and burnsleading to serious injuries that may require hospitalization. The elderly and children are especially atrisk since they may not recognize the dangers of a clothing fire and how to react quickly to extinguish theflames. Health and safety professionals are frequently asked to recommend reducing such risks. However,information about the flammability properties of non-FR treated clothing worn by the public is generallynot available. The objective of this research program was to develop a simplified method for definingthe flammability of commercially available fabrics. 50 samples were tested including Cotton, Wool, Silk,Nylon and Polyester. Changes in the weight of a sample resulting from combustion including the timeinvolved in the combustion cycle was used as a indictor of the total heat generated by the fire and therisk and severity of a burn injury. The results showed that the Cotton and Wool fabric samples createdthe highest risk of burn injury while the Polyester fabric created the lowest risk. These conclusions arebased on two criteria: Total time associated with a combustion cycle and the loss of fabric mass duringthe combustion cycle. The proposed method can be carried out using a standard laboratory fume-hood,a precision weight scale and a stopwatch.
Keywords: Fabric Fires; Fabric Flammability Assessment; Risk of Burn Injuries; Public Health